Online-learning at ISCTE-IUL: towards a sustainable education paradigm - Lopes, A. L.; Almeida, F.; Figueiredo, V. (Global forum Intelectual Capital 2019, 2019)
Online-learning platforms have long been praised for their great benefits, such as the way they contribute to long-distance students being able to overcome geographical barriers to their education, and the way they allow students to self-manage, by autonomously deciding when they enroll and complete courses. This empowers people from all over the world to engage in lifelong-learning that may have an important impact in their daily lives, especially in developing countries. Besides these benefits, there’s also an important dimension that is often overlooked: the contribution that the use of online-learning platforms has in providing a sustainable environment by reducing environmentally-damaging effects and the use of scarce resources. In this paper, we present the economical and environmental impact that the use of an online-learning platform has had in a public University in Lisbon, Portugal. We first present the online-learning platform that was developed in-house and follow up by describing the positive impact that this education paradigm has had in the lives of students, in reducing costs at the University, and in contributing to a more sustainable future.